Study of the Variability of Home Gardens Influencing Carbon Stock under Sub-humid Tropical Zone of West Bengal, India - Subba, Mohit; Pala, Nazir A.; Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2018)
The present study was delineated to explore the variability of carbon stock at home gardens in northern part of West Bengal spreading in the districts of Jalpaiguri, part of Cooch Behar and Siliguri sub-division of Darjeeling. The soil in the home gardens was acidic in reaction with mean pH of 5.8 and 6.0 at 0-20 and 20-40 cm depths, respectively. The mean available nitrogen, organic carbon content and soil carbon stock in the home gardens estimated at two soil depths was 173.61 and 103.05 kg N/ha, 1.16 and 0.87 % C and 26.24 and 19.49 Mg C/ha, respectively indicating their higher availability in the soil. Small sized gardens were estimated with highest amount of SOC (46.85 Mg/ha), while the amount of plant biomass carbon was highest in large gardens (60.38 Mg/ha). In terms of distance of home gardens from main road, plant biomass carbon was quantified highest in the gardens nearer to main road. The results of this study will not only benefit researchers and extension practitioners, but can also contribute to the policy platform to recognize the role of socio-psychological factors including home garden as climate change mitigation strategy.